HUBUNGAN ANTARA KONSEP DIRI (BODY IMAGE) DENGAN TINGKAT KECEMASAN PADA WANITA MENOPAUSE DI DESA MOTOLING II - Kundre, Rina; Hamel, Rivelino (Universitas Sam Ratulangi, 2019)
Abstract : Menopause is the last period or during the last menstrual period, one of the psychological aspects of a change in self-concept in the menopausal period is that menopausal women become worried about their bodies and form self-concept about how their bodies are.One of the psychological aspects of changing self-concept during menopause is that menopausal women become anxious about their bodies and form self-concepts about how their bodies are, maybe they look in the mirror every day and sometimes every hour.Research purposes This is to find out the relationship between self-concept and the level of anxiety during menopause in Motoling II Village. Research design the one used is descriptive correlation sampling technique that is by simple random method using two subjects of inclusion and exclusion with a lot of samples of 30 people. Research result using the chi-square test obtained between the self-concept and the level of anxiety in menopause p value = 0.001 <Î± = 0.005. Conclusion the results of this study indicate that there is a relationship between self-concept and anxiety level during menopause in Motoling II Village. Suggestion expected for Health workers in the Village Motoling II to pay more attention to women in Motoling II Village, especially women who are approaching menopause so there will be no lack of knowledge about what is meant by menopause. Keyword :The concept of self, levels of anxiety, MenopauseAbstrak : Menopause adalah haid terakhir atau saat terjadi haid terakhir, salah satu aspek psikologis dari perubahan konsep diri dimasa menopause sudah pasti wanita menopause menjadicemas mengenai tubuh mereka dan membentuk konnsep diri mengenai bagaimana keadaan tubuh mereka. Salah satu aspek psikologis dari perubahan konsep diri dimasa menopause sudah pasti wanita menopause menjadi cemas mengenai tubuh mereka dan membentuk konsep diri mengenai bagaimana keadaan tubuh mereka, mungkin mereka melihat kedalam cermin setiap hari dan kadang setiap jam. Tujuan Penelitian ini untuk mengetahui hubungan antara konsep diri dengan tingkat kecemasan pada masa menopause di Desa Motoling II. Desain Penelitian yang digunakan yaitu bersifat deskriptif kolerasi teknik pengambilan sampel yakni dengan cara simple random dengan menggunakan dua subjek inklusi dan ekslusi dengan banyak sampel 30 orang Hasil Penelitian mengguanakan uji chi-square didapat antara Konsep diri dengan tingkat Kecemasan pada masa menopause nilai p =0,001<Î± =0,005. Simpulan hasil penelitian ini menunjukan terdapat hubungan antara konsep diri dengan tingkat kecemasn pada masa menopause di Desa Motoling II Saran diharapkan bagi tenagah Kesehatan yang ada diDesa Motoling II agar lebih berperan aktif dalam meningkatkan pengetahuan wanita menopause supaya mengetahui dan menyadari perubahan yang terjadi.Kata Kunci : Konsep diri, Tingkat kecemasan, Menopause